THE PURSE-SEINE FISHERY FOR OIL SARDINE IN THE SOUTH KARNATAKA COAST AND ITS EFFECTS ON THE INDIGENOUS FISHERY - Dhulkhed, M H; Bhat, K Uma (Indian Journal of Fisheries, 2011)
With the introduction of purse seines in the midseventies the catches ofoil sardine steeply rose from 6,129 t in 1976-77 to 32,629 t in 1979-80. However,in the subsequent year the landings declined by 6,800 t and with increasein effort the catch rate only showed a downward trend, obviously because ofthe large-scale removal of gravid fish during 1978-79 and 1979-80. The totalinstantaneous rate of mortality was found to be high indicating the high rateof mortality caused by the gear. The adverse effect of purse seiners on traditionalfishery, with special reference to the shore-seine Rampart, is discussed